(untitled) (Contemporary Journal of Social Science Review, 2025)
The paper analyzes how U.S. juvenile justice policies contain embedded systemic racism through a study of the Juvenile Delinquency Act’s application in The Nickel Boys written by Colson Whitehead. Through its fictional narrative, the author presents an analytical view on juvenile reform facilities while exposing racial discrimination that pretends to work for rehabilitation. The research analyzes juvenile policy discrimination through the combination of Critical Race Theory (CRT) and Institutional Betrayal Theory (IBT) to understand how these equality-based policies functionally disadvantage the Black youth population through heavy punishment and long-term criminal consequences. The investigation focuses on four main issues that expose the racially discriminatory nature of JDA establishment while challenging the pretense of equal juvenile justice treatment and the organizational failures to monitor reforms, along with the way that racial policies push youths into adult justice systems. The fictional experiences of Elwood Curtis at Nickel Academy demonstrate juvenile justice facilities replicate harsh prison approaches by doing psychological hurt and physical harm that leads Black boys to encounter enduring social struggles. Research evidence demonstrates that replacing racially discriminatory language with race-neutral language within policy frameworks fails to stop racial bias because it lets systemic discrimination remain secret while continuing its operations. The book operates on multiple levels as literature while maintaining political relevance to real-life events similar to those found at Dozier School in Florida. The research supports substantial systemic adjustments and racial equality in juvenile justice by advocating for better reforms beyond policy rhetoric.